2017
DOI: 10.1021/acs.energyfuels.7b00097
|View full text |Cite
|
Sign up to set email alerts
|

Pelletizing Properties of Wheat Straw Blending with Rice Straw

Abstract: Mixing different types of biomass materials to achieve better pelletizing properties is a potential method to improve the biomass pelletizing process. In this study, experiments were carried out with a single pellet unit to obtain the pelletizing properties of wheat straw blending with rice straw. The effects of the temperature, pressure, moisture content, blending proportion, and particle size on specific energy consumption, pellet density, and compressive strength were investigated. The experimental data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Regarding non-woody blends, recent scientific findings have reported a generally low efficiency in comparison to woody-non-woody blends. Wang et al [89] reported an increase only in mechanical characteristics by mixing wheat and rice straw, while the LHV did not improve substantially. Similar results were presented by Lisowski et al [90] in relation to hay and straw mixing-a mechanical improvement without positive effects on LHV.…”
Section: Effects Of Blending and Binders On Pellet Qualitymentioning
confidence: 97%
“…Regarding non-woody blends, recent scientific findings have reported a generally low efficiency in comparison to woody-non-woody blends. Wang et al [89] reported an increase only in mechanical characteristics by mixing wheat and rice straw, while the LHV did not improve substantially. Similar results were presented by Lisowski et al [90] in relation to hay and straw mixing-a mechanical improvement without positive effects on LHV.…”
Section: Effects Of Blending and Binders On Pellet Qualitymentioning
confidence: 97%
“…The strength of single pellets for compressive loads was determined by diametric compression tests, which have been widely used by researchers [ 17 , 18 , 19 ]. The pellets were cut in 20 mm pieces using a scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported the pelleting of different types of biomass and their blends, with most of the studies focusing on material and process parameters including the mechanism of bonding from different viewpoints [2,[23][24][25][26][27]. Despite the numerous studies, the exact mechanism involved in bonding in biomass pellets and the source of inter-particle bonding relevant to pellet quality are not fully understood and still a subject of debate, particularly when the pellets are made from a blend of two or more different biomass materials.…”
Section: Purpose Of Studymentioning
confidence: 99%